Contemporary Irish women poets memory and estrangement - Collins, Lucy 1967- (Liverpool English texts and studies, 2016)
This book examines the intersection of private and public spheres through the representation of memory in contemporary poetry by Irish women. It explores how memory shapes creativity in the work of well-known poets such as Eavan Boland, Eiléan Ní Chuilleanáin and Medbh McGuckian as well as in that of an exciting group of younger poets